الاختلاط عبر التطبيقات الإلكترونية وضوابطه في ضوء القرآن والسنة : دراسة تحليلية - Nurul Hidayah Arom (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This research represents the concept of ikhṭilat or intermixing between men and women, and its restrictions. The researcher adopted two basic approaches: the inductive method and the analytical method. The inductive method used is by collecting Quranic verses with its interpretation, the Sunnah and its commentaries, and by collecting relevant research and dissertations. Meanwhile, the analytical method used is to analyse the information in this research. The researcher divided ikhṭilat into two categories: physical ikhṭilat and virtual ikhṭilat. Physical ikhṭilat is when men and women meet in real life, which means face to face interactions, while the virtual ikhṭilat happens in the virtual world, which is indirect meeting, through the internet by signing up using electronic applications. Considering the sins for an individual and a society in ikhṭilat, conversations between a man and a woman without need or desire, even gazing between the two genders, all of these are minor sins that could lead to fornication. Among the Sharia restrictions related to virtual ikhṭilat through electronic applications between the two genders are: lowering the gaze and quickly turning their sights from looking at the opposite gender, even if only looking at a picture, avoiding seclusion, avoid softening the voice for women, avoid dazzling displays like the times of ignorance (jahiliyyah), and concealing adornments and virtues. These restrictions would ensure communication between the two genders is in accordance with the Sharia restrictions that will guarantee peace and tranquillity in life from any obscenity and disobedience, in line for forgiveness and blessing of God Almighty.